The Analysis of the Urgency of Multicultural Education in the Families of Converts and Its Relevance to Islamic Values - Linaci, Ahmad Novta Sebad; Octia, Aniesya; Fathurrohman, Asep; Alfusanah, Fadilatul; Tadjuddin, Nilawati; Sagala, Rumadhani; Abbas, Erjati (The Future of Education Journal, 2024)
Indonesia is one of the largest multicultural countries in the world, the truth of this statement can be seen from the socio-cultural and geographic areas which are so diverse and broad. With a population of approximately 13,000 large and small islands in the Republic of Indonesia, and a population of approximately 200 million people, it consists of 300 tribes who speak almost 200 different languages. In otherwise, adhere to various religions and beliefs such as Islam, Catholicism, Protestant Christianity, Hinduism, Buddhism, Confucianism, as well as various kinds of beliefs. Multicultural education is a progressive approach, this approach is in line with the principles of education implementation contained in the 2003 law and education system (SISDIKNAS) article 4 paragraph 1, which states that education is carried out democratically and fairly and is not discriminatory by upholding human rights (human rights), religious values, cultural values, and national pluralism. Family converts to Islam are those who are bound to embrace Islam or strengthen their belief in Islam. In the process of religious conversion that each person does not happen by chance, but rather the conversion is driven by several different processes and conditions. Multicultural education normatively aims to promote understanding and respect for cultural diversity. It doesn't just stop there, multicultural education has a mission, including teaching values such as tolerance, respect and awareness of diversity. Islam, as a universal religion, highly upholds human values, equal rights, and recognizes the diversity of cultural backgrounds and pluralism.